(untitled) (Indian Journal of Animal Production and Management, 2016)
A feeding trial was conducted to evaluate the effect of guar meal, an unconventional protein source on health and carcass characteristics of local kids. 3 months old kids divided into three equal groups (control, T1 and T2) randomly were fed concentrate mixture containing ground nut cake (control) while in T1 and T2, ground nut cake was replaced with guar meal at 50 and 100 %, respectively. Significantly (P<0.05) higher dressing percentage was recorded on slaughter basis in group T1. The results showed that dietary treatments had no effect on whole cuts and non-edible portion. There was significantly (P<0.05) higher edible portion in group T1 compared to other groups. No significant difference was observed in yield of visceral organs among the groups. Bone: muscle ratio was higher (P<0.05) in group T1. Histopathology revealed cellular swelling and peripheral leucocytic infiltration in liver of T2 group kids. Present study revealed that ground nut cake can be replaced with guar meal, an unconventional feed at 50% level in kids ration without any adverse effect.